(untitled) (City: History, Culture, Society, 2021)
Over recent years, during a number of projects carried out by the Ukrainian Center for Holocaust Studies, evidence have been identified about more than 140 sites of muss murder of Roma in the German-occupied areas of Ukraine. In result, five maps were compiled which are presented in the article. The maps fill up the gaps in the cartography and historiography on the subject of Roma genocide, and allow us to illustrate and answer the following questions that are urgent in describing the bitter fate of the Roma population of Ukraine: (1) Location of Roma killing sites (which is important to apprehend the scope, regional features and statistical aspects of the Roma genocide in Ukrainian territory); (2) The distribution between nomadic and settled Roma victims, according to available sources (which is important given the conceptual discussions in historiography on the principles of the Nazi “Gypsy” policies; the predominance of the settled victims convincingly demonstrates that in perpetrators’ mindset the racial and ideological motivations prevailed over notions of “asociality” of individual Roma); (3) Distribution between German perpetrators and local accomplices in crimes against Roma (which is important in the context of the attitude of the local population towards the persecuted Roma, and the degree of initiative of local governments and auxiliary police in genocidal actions); (4) The institution that documented the crimes (which is important from the perspective of the agency and state policies on documenting crimes against Roma people – particularly, documentation completeness and representativeness – and thus shaping of public opinion about it); (5) Availability of memorials at the killing sites of Roma victims, or indication of Roma among the victims (which is important in the context of the formation of social memory of Roma genocide and the presence / absence of “cultural memory” tools to commemorate victims). Each map is accompanied by commentary of what method was used to compile it, as well as analysis of the scholarly meaning of the information presented. Be the maps used together or separately, they carry the potential for use in research, educational, or museum activities.